Carência de professores licenciados em Matemática em Corrente: um estudo a partir das representações sociais - Flavio de Ligorio Silva (2018)
The phenomenon of the teachers licensed in mathematics lack in Corrente, a city in the extreme south of Piaui, is the object of investigation of this thesis. This is a qualitative research, involving a group of eleven teachers working in public schools in the region, subdivided between teachers and managers. Initially, information about the municipality and historical data on the education of Piaui, from colonization to redemocratization in 1985, was presented with the purpose of establishing the description of the research scenario. The mathematics teachers lack in Corrente was observed from the perspective of Moscovicis theory of social representations, considering his procedural approach, and Jodelets (2001), adopted as the main reference, in addition to other authors. Studies on the career and the teaching condition were established as presuppositions, evidencing the question of the replacement and professional attractiveness, the adequacy of teacher training, the precariousness of its working conditions, shortage of teachers, as well as the analysis carried out by other authors on the plans that regulate the teaching career in the public institutions, in other contexts. For the obtaining of data, the narratives produced by the subjects in unstructured and semi-structured interviews were prioritized, with a subsequent content analysis as recommended by Bardin (2016). The results showed a set of representations about the lack, linking it to other representations, such as the conception of teaching as partial work and source of complementary income, the question of its low professional attractiveness, as well as the improvised formation of many teachers who teach mathematics in the region. There are also mismatch between local training options and the labor market, the depreciation of teachers and the work they do, the use of public employment to control the public machine, and the hegemony of the ruling political class in a situation of political patronage, personalism and physiology, among others. These representations are also anchored in a negative perspective of mathematics and its teaching, objectified under the sign of the "seven-headed bug" or "boogeyman", and evidenced the teaching-learning conceptions linked to the teacher centered pedagogy, as theorized by Becker (2012a).